2000
DOI: 10.1177/147323000002800102
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass and Global Function in Essential Hypertension after Antihypertensive Therapy

Abstract: This study compares left ventricular global function in 55 patients (25 with hypertrophy and 30 without hypertrophy) with essential hypertension, whose blood pressure had been stable for longer than 1 year, with that in 35 healthy subjects. Left ventricular global function was calculated using the echocardiographic Doppler index as described by Tei et al. (Tei index). No significant differences were observed in echocardiographic left ventricular systolic function between the three groups. Left ventricular glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Although left ventricular systolic function reflected by fractional shortening did not differ between the healthy subjects and the hypertensives in this study, the flow Doppler Tei index was similar between groups at either position. In this study and the report by Yakabe et al, 13 age was not a significant determinant of traditional Tei index. In contrast, in a study with a larger population of a wider age spectrum, Spencer et al 14 demonstrated a moderately positive correlation between age and the Tei index obtained from averaged left ventricular acoustic quantification waveforms.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Although left ventricular systolic function reflected by fractional shortening did not differ between the healthy subjects and the hypertensives in this study, the flow Doppler Tei index was similar between groups at either position. In this study and the report by Yakabe et al, 13 age was not a significant determinant of traditional Tei index. In contrast, in a study with a larger population of a wider age spectrum, Spencer et al 14 demonstrated a moderately positive correlation between age and the Tei index obtained from averaged left ventricular acoustic quantification waveforms.…”
Section: Discussionsupporting
confidence: 59%
“…Yakabe et al demonstrated that the patients with essential hypertension whose left ventricular systolic function was normal had a higher flow Doppler Tei index than the healthy subjects 13 . Although left ventricular systolic function reflected by fractional shortening did not differ between the healthy subjects and the hypertensives in this study, the flow Doppler Tei index was similar between groups at either position.…”
Section: Discussioncontrasting
confidence: 55%
“…4) Several previous studies have demonstrated that the Tei index is abnormal even in hypertensive patients without overt heart disease. [5][6][7] However, there have been few studies 8) regarding the influences of hypertension on the Tei index in lifestyle-related diseases such as hypertension. The Tei index is not affected by LV loading conditions such as LV preload 9) or blood pressure 10) in patients who show impaired LV systolic function due to myocardial infarction or heart failure.…”
mentioning
confidence: 99%
“…Consequently, the existence of a clinically applicable method for assessment of global myocardial performance in patients with AMI would be very useful. Such a method is the systolic‐diastolic Doppler Index (DI) or Tei index, which has been studied in several cardiac diseases 34–44 and has been proved to have both predictive value 34 , 37 , 44 in patients with LV dysfunction and good correlation with global LV performance 34, 35 . Moreover, there is evidence that this index is more sensitive than mitral E, A waves and deceleration time of E wave for the assessment of LV diastolic function and has a better correlation with—dp/dt and tau 45 .…”
mentioning
confidence: 99%